CFD ANALYSIS OF PULVERIZED COAL COMBUSTION IN A BLAST FURNACE TUYERE: COMPARISON BETWEEN WSGG AND GG MODELS FOR RADIATION MODELING - da Silva, C. V.; Weber, G.; Centeno, F. R.; França, F. H. R. (Revista de Engenharia Térmica, 2016)
Combustion processes are being employed for many years, and remains a major source of energy for industrial operations through the conversion of chemical energy in thermal energy, besides being usually accompanied by formation of pollutants. This work presents a numerical investigation using the software Ansys CFX to model the process of combustion of pulverized coal injected into a blast furnace for production of pig iron making a comparison between WSGG and GG spectral models for gas radiation aim to verify the influence on the radiation heat transfer and the temperature field. Since global coal reserves are being constantly reduced, new techniques using coal are being studied. Among some effective techniques, there is the injection of pulverized coal through a tuyere installed at the bottom of the blast furnace. Thus, among the objectives of this work is to obtain information about the pulverized coal burning process injected. Firstly, it will be employed a North American coal as a base case in order to better understand the involved phenomena. Simulations were made using the actual operating conditions of a blast furnace, which uses atmospheric air enriched with oxygen for burning the coal. The same boundary conditions and operation of other investigations were considered in order to validate the model developed for this work, and so that it can be applied in similar situations, either in assessments or in projects of coal injection systems and combustion in blast furnaces. The results include temperature and velocity fields, oxygen concentration, and the formation of CO and CO2 and they are in agreement with data from literature. Comparing the results of this study with the results obtained in the work (Gu et al., 2010) It observed a qualitative similarity between them and also quantitative. Furthermore, it was found that, in this case, modeling the absorption spectrum of the combustion gases resulting in changes in flame form, but did not significantly alter the magnitude of temperatures, since the walls of the equipment are considered adiabatic.